Magnitude Squared of Coherence to Detect Imaginary Movement. (13th July 2009) - Santos Filho, Sady Antônio; Tierra-Criollo, Carlos Julio; Souza, Ana Paula; Silva Pinto, Marcos Antonio; Cunha Lima, Maria Luiza; Manzano, Gilberto Mastrocola
Abstract : This work investigates the Magnitude Squared of Coherence (MSC) for detection of Event Related Potentials (ERPs) related to left-hand index finger movement. Initially, ERP presence was examined in different brain areas. To accomplish that, 20 EEG channels were used, positioned according to the 10–20 international system. The grand average, resulting from 10 normal subjects showed, as expected, responses at frontal, central, and parietal areas, particularly evident at the central area (C3, C4, Cz). The MSC, applied to movement imagination related EEG signals, detected a consistent response in frequencies around 0.3–1 Hz (delta band), mainly at central area (C3, Cz, and C4). Ability differences in control imagination among subjects produced different detection performance. Some subjects needed up to 45 events for a detectable response, while for some others only 10 events proved sufficient. Some subjects also required two or three experimental sessions in order to achieve detectable responses. For one subject, response detection was not possible at all. However, due to brain plasticity, it is plausible to expect that training sessions (to practice movement imagination) improve signal-noise ratio and lead to better detection using MSC. Results are sufficiently encouraging as to suggest further exploration of MSC for future BCI application.